A roadmap for bio‐medical waste management research. (14th April 2021) - Shwetmala, Kashyap; Arkalgud, Ramaprasad; Anilkumar, Munikrishnappa
Abstract: Bio‐Medical waste is solid or liquid waste generated from healthcare activities. Bio‐Medical waste management (BMWM) is necessary to protect local community health and environment, to reduce its financial loss and to preserve its social and aesthetic values. BMWM encompasses the waste generation, segregation, collection, transportation, processing and disposal. The BMWM system is complex and challenging. The research on BMWM must address the complexity for the solutions to be effective. We present an ontology of BMWM to visualize the complexity of the system and analyse it systematically. The research corpus of all the 184 articles from Scopus on BMWM is mapped onto the ontology. Ontological and theme maps are generated to highlight the emphases and gaps in the research. The results show the roadmap of BMWM research with the dominant emphasis on its functional elements and outcomes. There is little emphasis on the composition of the waste, the stakeholders and the policy instruments that guide and regulate the system. Correcting the biases in the present research corpus will help develop effective research and practice. This review results can be used to develop a roadmap for research to improve the BMWM system.